Pometia pinnata Leaf Extract As a Natural Larvicide For aedes aegypti Mosquitoes, A Vector Of Dengue Haemorrhagic Fever (DHF) Disease - Ukratalo, Abdul M; Manery, Dodikrisno E; Syuaib, Achmad; Muhammad, Alfaro; Nanere, Bill E; Assagaf, Abdur Rahman (Medicor : Journal of Health Informatics and Health Policy, 2024)
Dengue Haemorrhagic Fever (DHF) is a rapid-onset infection caused by the Dengue virus that can lead to severe shock and even death. Pometia pinnata, a plant found in the Maluku region, possesses untapped therapeutic potential despite the presence of secondary metabolite chemicals believed to have larvicidal properties. This study aims to evaluate the biolarvicidal efficacy of the leaf extract of Pometia pinnata against Aedes aegypti's larvae, a DHF carrier. The extraction process used the maceration technique employing ethanol as the solvent. A larvicidal experiment was performed to evaluate the bioactivity against Aedes aegypti larvae. The findings indicated that the leaf extract of Pometia pinnata possesses larvicidal properties against Aedes aegypti larvae, as evidenced by an LC50 value of 0.101%. The results offer insights into the possible utilisation of Pometia pinnata leaf extract as a viable source of active compounds for developing biolarvicides to control dengue vectors.